A System-Based Analysis of Nonformal Learning: Evaluating The Input-Process-Output-Outcome Model in A Private Tutoring Institution in Indonesia (Indonesian Journal of Adult and Community Education, 2025)
This study examines the learning system of a private tutoring institution in Indonesia using the Input–Process–Output–Outcome (IPOO) framework. Employing a qualitative descriptive design, data were collected through in-depth interviews, observations, and document analysis involving institutional leaders, tutors, and students. The findings reveal that the tutoring institution operates as a highly structured and standardized system supported by selective inputs, intensive instructional processes, and technology-enhanced learning.From the input perspective, student motivation, tutor quality, and centralized curriculum design play a crucial role in shaping learning effectiveness. The process dimension is characterized by performance-oriented instruction, including intensive practice, exam-focused strategies, and continuous evaluation. While these approaches contribute to measurable improvements in academic performance, they also indicate a tendency toward procedural learning rather than deep conceptual understanding.A key contribution of this study is the identification of digital mediation as a critical component that strengthens the relationship between learning processes and outcomes. In addition, student motivation functions as a moderating factor influencing engagement and learning effectiveness across all IPOO dimensions. The results further show that although the tutoring system enhances academic performance and increases access to higher education, outcomes remain influenced by external factors such as competition and individual differences.This study extends the traditional IPOO framework by proposing a more dynamic model that integrates digital and motivational dimensions. The findings highlight the need for nonformal education systems to balance performance-oriented instruction with meaningful learning experiences.